2016
DOI: 10.25215/0401.136
|View full text |Cite
|
Sign up to set email alerts
|

Role of Emotion Regulation in Quality of Life

Abstract: The purpose of this study was to investigate the association between Emotion Regulation and quality of life. Five hundred and thirty-eight adults, 262 men and 276 women, selected through random sampling method participated in the study. Emotion Regulation Questionnaire (ERQ) and Quality of Life-BREF scale (WHOQOL-BREF) were used to gather data. Results of the study revealed a significant correlation between the variables; however, reappraisal showed a positive relationship with quality of life while suppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Further, it was revealed that an increase in acceptance was highly significantly linked with an increase in depression, anxiety, stress and poorer quality of life, which is consistent with previous literature ( Domaradzka & Fajkowska, 2018 ; Dubey, Podder & Pandey, 2020 ; Manju, 2017 ). Although acceptance is an adaptive strategy, few studies suggested that acceptance should be treated as maladaptive ( Martin & Dahlen, 2005 , Tuna & Bozo, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…Further, it was revealed that an increase in acceptance was highly significantly linked with an increase in depression, anxiety, stress and poorer quality of life, which is consistent with previous literature ( Domaradzka & Fajkowska, 2018 ; Dubey, Podder & Pandey, 2020 ; Manju, 2017 ). Although acceptance is an adaptive strategy, few studies suggested that acceptance should be treated as maladaptive ( Martin & Dahlen, 2005 , Tuna & Bozo, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…It encompasses emotional control, anger management, and impulse control. Manju and Basavarajappa (2016) reported that reappraisal, a facet of emotional regulation, was positively associated with various quality of life domains, including physical and psychological health, as well as social and environmental relationships. However, the suppression domain in emotional regulation negatively correlated with the environmental aspect of quality of life.…”
Section: Path Coefficientmentioning
confidence: 99%
“…A study conducted in Indonesia states that there is an influence of emotional regulation on improving the quality of life of patients with chronic diseases 6 and a study conducted in India states that there is a significant association between regulation of emotions and the quality of one's life. 5 A qualitative study conducted in Jakarta shows that cervical cancer and its treatment have emotional consequences related to chronic conditions that they experience and can have a psychological impact on women who have undergone cervical cancer therapy. 17 The results of other qualitative studies conducted in Surabaya state that most women who suffer from cervical cancer feel themselves in a crisis period that requires adjustment.…”
Section: Original Articlementioning
confidence: 99%